Study The Of The Effect Of Non-Performing Loans On The Efficiency Of Banking Profits (An Applied Study On Traditional Syrian Private Banks) - Al- Rifaai, A.H.M; Ghadban, Obada Samee (Latakia University Journal - Economic and Legal Sciences Series, 2019)
This research seeks to highlight the impact of non-performing loans on the efficiency of profits (alternative and standard), as non-performing loans became the focus of all banks because of their impact on financial performance. The study was conducted on traditional private banks in the Syrian Arab Republic during the period from 2005 to 2016. In the first stage, the efficiency of alternative and standard profits was estimated using the Stochastic Frontier Analysis (SFA) method. In the second stage, the Tobit Regression Model regression analysis is used to detect the effect of non-performing loans on profit efficiency, where the most important results: - There were significant statistical differences in Profit efficiency of alternative and standard between traditional private banks. - Negative impact of non-performing loans on profit efficiency (alternative and standard). - The use of the Stochastic Frontier Analysis (SFA) method in estimating the efficiency of alternative and standard better than the use the Least Square Method, which aims to separate the components of the error from the case of inefficiency. - The efficiency of alternative profit is higher than the profit efficiency on average for the study period and according to averages for each year. يسعى هذا البحث إلى إبراز أثر القروض المتعثرة على كفاءة الأرباح (البديلة والمعيارية) حيث أصبحت القروض المتعثرة محل اهتمام كل المصارف وذلك لما لها من تأثير على الأداء المالي، وتم إجراء الدراسة على المصارف الخاصة التقليدية في الجمهورية العربية السورية خلال الفترة من عام 2005 لغاية 2016 وذلك باتباع منهج من مرحلتين ، في المرحلة الأولى تم تقدير كفاءة الأرباح البديلة والمعيارية من خلال استخدام طريقة حد التكلفة العشوائيSFA )Stochastic Frontier Analysis )، أما في المرحلة الثانية تم استخدام تحليل انحدار Tobit Regression Model للكشف عن أثر القروض المتعثرة على كفاءة الأرباح، حيث كانت أهم النتائج: v وجود فروق ذات دلالة إحصائية في كفاءة الأرباح البديلة والمعيارية بين المصارف الخاصة التقليدية. v وجد أثر سلبي للقروض المتعثرة على كفاءة الأرباح (البديلة والمعيارية). v إن استخدام طريقة حد التكلفة العشوائي في تقدير كفاءة الأرباح البديلة والمعيارية أفضل من استخدام طريقة المربعات الصغرى، حيث تهدف إلى فصل مكونات الخطأ عن حالة نقص الكفاءة. v أن كفاءة الربح البديل أعلى من كفاءة الربح المعياري بالمتوسط لفترة الدراسة وأيضاً حسب المتوسطات لكل سنة.